“I was waiting for my period”: Understanding pregnancy recognition among adolescents seeking abortions in Ethiopia, Malawi, and Zambia(,☆☆) - Strong, Joe (Contraception, 2023)
OBJECTIVES: For a person seeking an abortion, the ability to recognize a pregnancy is a critical first step. Pregnancy recognition is complex and shaped by numerous factors. This paper explores the experiences of pregnancy recognition among adolescents in Ethiopia, Malawi, and Zambia. STUDY DESIGN: The final sample included 313 adolescents aged 10 to 19 who had sought abortion-related care at urban public facilities in Ethiopia (N = 99), Malawi (N = 104), and Zambia (N = 110). Researchers collected mixed-method data on how adolescents came to recognize that they were pregnant and thematically analyzed qualitative data alongside descriptive statistics from quantitative data. RESULTS: Most adolescents reported that their main mode of recognizing a pregnancy was medical pregnancy tests or late menstruation. Reasons for not recognizing a pregnancy included irregular menses or recent menarche and attribution of signs and symptoms to other medical conditions. Psychological barriers to pregnancy recognition were important, including the refusal to accept a pregnancy and denial of a pregnancy. Timing of recognition shaped the abortion care available for adolescents and the affordability of care. For some adolescents, their capacity to recognize their pregnancy led to involuntary or voluntary disclosure, which decreased their reproductive autonomy. CONCLUSIONS: Adolescent experiences of pregnancy recognition complement existing evidence, illustrating critical barriers across age and context. Interrogating pregnancy recognition among adolescents exposed the critical implications for the availability, accessibility, affordability, and autonomy of their abortion trajectory. IMPLICATIONS: Pregnancy recognition is complex and can influence adolescents’ ability to exercise their reproductive rights and access abortion care of their choosing. Programmes to improve awareness of the signs of a pregnancy, increasing the provision of affordable and accessible pregnancy testing and further research on pregnancy recognition are necessary to support adolescents’ reproductive autonomy.